MODERN ISLAMIC EDUCATION IN THE ERA OF SOCIETY 5.0: CHALLENGES, OPPORTUNITIES, AND STRATEGIC TRANSFORMATION - Abdul Fatah (Adisam Publisher, 2026)
The emergence of Society 5.0 has significantly transformed educational systems by integrating digital technology, artificial intelligence, big data, and human-centered innovation. In this context, modern Islamic education faces major challenges and opportunities in adapting to technological advancement while maintaining Islamic moral and spiritual values. This study aims to analyze the challenges, opportunities, and strategic transformation of modern Islamic education in the era of Society 5.0. The research employed a qualitative approach using the library research method, examining various scholarly sources, including Scopus-indexed journal articles, books, and other relevant academic publications on Islamic education, digital transformation, and educational innovation. The findings indicate that modern Islamic education is undergoing substantial transformation through the implementation of digital learning systems, technology integration, and innovative pedagogical approaches. However, several challenges remain, including limited technological infrastructure, low digital literacy, issues with curriculum adaptation, and concerns about moral degradation from uncontrolled digital exposure. The study also reveals that Society 5.0 offers significant opportunities to improve educational accessibility, learning flexibility, digital competence, and interdisciplinary collaboration. Strategic transformation in Islamic education, therefore, requires curriculum reform, teacher competency development, institutional innovation, and the integration of Islamic ethical values with technological advancement. The study concludes that modern Islamic education must adopt a human-centered, value-oriented approach to produce graduates who are intellectually competent, technologically adaptable, morally responsible, and spiritually grounded in responding to global challenges in the digital era.